Effect of a notch at the distal end of a microcatheter on vein deformation in segmental adrenal venous sampling: a preliminary study using computational fluid dynamics. - Kinoshita, Tomo; Seiji, Kazumasa; Putra, Narendra Kurnia; Watanabe, Tomohito; Matsumoto, Sho; Ohta, Makoto; Takase, Kei (Medical & Biological Engineering & Computing, 2019)
This study aimed to evaluate the effect of a notch at the distal end of a microcatheter on vein deformation in segmental adrenal venous sampling. A three-dimensional fluid-structure interaction simulation was performed using commercial finite element software. A computational model of a vein with a catheter inserted into it was constructed. The outer and inner diameters of the vein were 0.9 mm and 0.6 mm, respectively, whereas those of the catheter were 0.6 mm and 0.5 mm, respectively. The velocity of the blood flow at the outlet was 85 mm/s. The pressure at the inlet was 0 Pa. The mesh consisted of approximately 660,000 elements. The effect of the number (0-4) and shape (no notch, 1/4 circular, 1/3 circular, semicircular, 2/3 circlecircular, and 3/4 circular) of the notches at the distal end of the microcatheter on the vein deformation when a suction pressure was applied was evaluated. The venous wall displacement was the smallest with the one-notch catheter, followed by the four-notch catheter, and was the smallest with the catheter having 1/4-circular notches, followed by the one with 1/3-circular notches. In conclusion, microcatheters having one notch and 1/4-circular notches reduce vein deformation and lead to successful segmental adrenal venous sampling. Graphical abstract Comparing catheters having different notch shapes.